David the Invincible, commentary on Aristotle's Prior analytics : critical Old Armenian text - David, the Invincible. (Philosophia Antiqua, 2010)
David the Invincible's (6th century AD) Commentary on Aristotle's Prior Analytics survives only in an old Armenian translation from Greek. Its critical edition with a Russian translation (1967) was based on the editio princeps of Venice (1833) and five manuscripts of the Matenadaran (Institute of Ancient Manuscripts, Erevan). This edition includes the text of 1967, revised through careful rechecking of the same five manuscripts and the editio princeps, as well as on the basis of twenty-three other manuscripts. The book contains the first English translation of the work, textual parallels with other commentaries on Aristotle, trilingual (Armenian, Greek, English) glossaries and other material useful to interested specialists. The introduction, among other subjects, discusses the disputable issues of authorship and the translator.